PROTOCOL: Effectiveness of nutrition counselling for pregnant women in low‐ and middle‐income countries to improve maternal, infant and child behavioural, nutritional and health outcomes: A systematic review. Issue 4 (9th November 2021) - Dewidar, Omar; Saad, Ammar; Baqar, Aqeel; John, Jessica C.; Riddle, Alison; Ota, Erika; Kung'u, Jacqueline K.; Arabi, Mandana; Raut, Manoj K.; Klobodu, Seth S.; Rowe, Sarah; Busch‐Hallen, Jennifer; et al.
Abstract: The objective of this systematic review is to identify, appraise and synthesise the best available evidence on the effectiveness of nutritional counselling and education interventions on maternal, infant and child health outcomes, and assess the differences in effects across participants' PROGRESS+ characteristics. To achieve these objectives, we will aim to answer the following research questions: What is the effectiveness of nutrition counselling interventions for pregnant women in low‐ or middle‐income countries on maternal, infant and child health outcomes? What are the impacts of nutrition counselling interventions on maternal, infant and child health outcomes across participants' PROGRESS+ characteristics?